Aktivitas Antibakteri Ekstrak Padina australis terhadap Isolat Bakteri Pembusuk Ikan Tongkol (Euthynnus affinis) - Tamaya, Reni; Sriwulan (Biotropic : The Journal of Tropical Biology, 2026)
Padina australis is a brown algae that has secondary metabolites such as phenols, tannins, flavonoids, saponins, and alkaloids that have antibacterial potential. This study aims to determine the antibacterial activity of Padina australis extract against spoilage bacteria of tuna (Euthynnus affinis) from genus Staphylococcus sp. and Bacillus sp. through disc diffusion method. Data on the diameter of the inhibition zone were analyzed statistically. The results showed that Padina australis extract was able to produce an inhibition zone in both isolates, but the antibacterial activity was relatively weak (≤ 5mm). The 60% extract concentration produced the highest inhibition zone of 2.07 mm in Staphylococcus sp. and 2.23 mm Bacillus sp. isolates, while the positive control produced strong to very strong antibacterial activity, with diameters of 19.28 mm and 33.76 mm. The results of statistical analysis showed that variations in extract concentration did not significantly affect the inhibition zone in both isolates (p = 0.119 and p = 0.160). The low antibacterial activity is likely due to limited content of bioactive compounds, the extraction method, and suboptimal diffusion of the extract on the agar medium. Padina australis extract has the potential as a natural antibacterial, but its effectiveness still needs to be improved with further optimization.